Penerapan Integral Lipat Dua dalam Prediksi Jumlah Penduduk di Kota Tebing Tinggi Tahun 2030 : Visualisasi 3D Menggunakan Geogebra - Petra Putri Sarinah Pandiangan; Alvi Sahrin Nasution; Grace Amelia Purba; Rizka Nabila Damanik; Endang Lyfia Saragih; Farel Al Azmi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Tebing Tinggi City, which has a strategic position in North Sumatra, is experiencing changes in population growth that need to be predicted for development planning purposes. The purpose of this study is to forecast the population of Tebing Tinggi City in 2030 by applying the Double Integral method, and visualize the results in 3D using GeoGebra. The method used is a quantitative approach with a case study, where the population density function is created based on secondary data from the Central Statistics Agency (BPS) of Tebing Tinggi City for the period 2010 to 2024. Data on area and population per sub-district are used to develop a population growth model calculated using the double integral. The forecast results show that the population of Tebing Tinggi City is estimated to reach 26,038 people in 2030, with varying growth rates in each sub-district. 3D visualization through GeoGebra is able to depict the distribution of population density in an interactive geometric form, thus facilitating the understanding of complex mathematical concepts. The conclusion of this study is that double integrals can be applied effectively to predict population size, and GeoGebra serves as a very useful visual aid in presenting the results of multivariable calculus analysis.